Questioning Divine dei͂: On Allowing Texts Not to Say Everything - Smit, Peter-Ben 1979- (2019)
Frequently, δεῖ is associated with salvation history and the exercise of divine will and identified as “theological δεῖ” or “divine δεῖ”. In the history of scholarship, there is an increasing emphasis on interpreting δεῖ along these lines, thereby marginalizing other shades of meaning that this verb may have. The question is whether this course of interpretative action is justified. This will be tested in this article. In order to do so, first a brief overview of the possible shades of meaning of δεῖ will be provided; second, the occurrences of δεῖ in the Gospel of Mark are systematically reviewed; third and finally, concluding reflections will be offered, including a word of caution when it comes to deifying δεῖ. In this manner, the current study seeks to contribute to the undoing of the theosis of this particular part of early Christian vocabulary.
Keywords: Gospel of Mark; Greek lexicography; Determinism; Divine Will; Hermeneutics; history of interpretation; Predestination; Salvation History; theological δεῖ